2020
DOI: 10.1021/acs.inorgchem.0c02440
|View full text |Cite
|
Sign up to set email alerts
|

Sterically Encumbered Tris(trialkylsilyl) Phosphine Precursors for Quantum Dot Synthesis

Abstract: The synthesis of nanomaterials with a narrow size distribution is challenging, especially for III−V semiconductor nanoparticles (also known as quantum dots). Concerning phosphides, this issue has been largely attributed the use of overly reactive precursors. The problem is exacerbated due to the narrow range of competent reagents for III−V semiconductor syntheses. We report the use of sterically encumbered tris(triethylsilyl) phosphine and tris(tributylsilyl) phosphine for InP quantum dot (QD) synthesis among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 51 publications
0
18
0
Order By: Relevance
“…, tris(trimethylsilyl)phosphine (TMS 3 P) as a common P precursor) 19 hinders this separation, favors Ostwald ripening, and, hence, broadens the size distribution of InP QDs. Although Ostwald ripening can be avoided through the use of less reactive P precursors such as tris(trimethylgermyl)phosphine, tri(pyrazolyl)phosphane, aminophosphine, and white phosphorus, 20–25 the optical properties of the resulting InP QDs do not satisfy industrial criteria.…”
Section: Introductionmentioning
confidence: 99%
“…, tris(trimethylsilyl)phosphine (TMS 3 P) as a common P precursor) 19 hinders this separation, favors Ostwald ripening, and, hence, broadens the size distribution of InP QDs. Although Ostwald ripening can be avoided through the use of less reactive P precursors such as tris(trimethylgermyl)phosphine, tri(pyrazolyl)phosphane, aminophosphine, and white phosphorus, 20–25 the optical properties of the resulting InP QDs do not satisfy industrial criteria.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, processed InP core QDs were etched with a small quantity of ammonium bifluoride (∼8 mg) in a solution of 0.137 g of myristic acid in 10 mL of ODE at 60 °C overnight. 28 This decreased the size to ∼1.7 nm diameter. Next, the sample was processed via precipitation with dry ethanol.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It was found that processing core QDs and treating their surfaces with various metal salts resulted in minimal impact on their optical properties (see Figure S8A). As a result, processed InP core QDs were etched with a small quantity of ammonium bifluoride (∼8 mg) in a solution of 0.137 g of myristic acid in 10 mL of ODE at 60 °C overnight . This decreased the size to ∼1.7 nm diameter.…”
Section: Introductionmentioning
confidence: 99%
“…36,37 Various moderate alternative etchants have been examined such as 1-hexyl-3methyl-imidazolium tetrafluoroborate, 38 carboxylic acid, 39,40 and ammonium bifluoride. 41 However, these InP plain core QDs are generally unstable and require additional epitaxial growth of inorganic shells to avoid fast fluorescence degradation under ambient conditions. Recently, Won et al developed a method of introducing hydrofluoric acid as the etchant to eliminate the oxidized surface of InP cores, on which ZnSe and ZnS shells were grown consecutively at high temperature.…”
mentioning
confidence: 99%